Perceptions of the Slow Food Cultural Trend among the Youth - Lelia Voinea; Anca Atanase; Ion Schileru (Amfiteatru Economic Journal, 2016)
As they become increasingly aware of the importance of healthy eating and of the serious food imbalance caused by the overconsumption of industrial, ultra-processed and superorganoleptic food, consumers are now beginning to turn their attention to food choices guaranteeing both individual health and also of the environment . Thus, in recent years we are witnessing the rise of a cultural trend - Slow Food. Slow Food has become an international movement that advocates for satisfying culinary pleasure, protects biological and cultural diversity, spread taste education, links green producers to consumers and believes that gastronomy intersects with politics, agriculture and ecology. Slow Food proposes a holistic approach to food problem, where the economic, sociocultural and environmental aspects are interlinked, being pursued as part of an overall strategy. In order to highlight the manner in which the principles of this cultural trend are perceived by the representatives of the new generation of consumers in Romania, exploratory research marketing was conducted among the students in the second year of the master's program Quality Management, Expertise and Consumer Protection, from the Faculty of Business and Tourism from the Buchares t University of Economic Studies . The results of this research have shown an insufficient knowledge of Slow Food phenomenon and, especially, the Slow Food network activity in Romania. To show that the Slow Food type of food is a healthier option towards which the future consumer demand should be guided, especially those belonging to the younger generation, an antithetical comparative analysis of the nutritional value of two menus was performed: a suggestive one for the Slow Food feeding style and other one, specific to the fast food style. Slow Food style was considered antithetical to the fast food because many previous studies have shown a preference of the young for the fast-food type products, despite the nutritional imbalance they generate. Comparative analysis of nutrition was produced by using the coverage degree method and the results have shown that the Slow Food type menu is a balanced food option. Given the issues that we highlighted, this paper can be a reference point in our endeavor to increase the awareness of the Romanian young people regarding the need to create a sustainable food system, in economic, environmental and socio-cultural point of view, as well as their orienting towards natural and healthy food options.
Keywords: L83; M31; Z32; 330; Slow Food; Fast Food; healthy food; consumer perception; analysis of the nutritional value; coverage degree method